2015
DOI: 10.1111/1759-7714.12264
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib versus platinum‐based double‐agent chemotherapy as the first line treatment in advanced anaplastic lymphoma kinase‐positive lung adenocarcinoma

Abstract: BackgroundTo explore the efficacy and safety of crizotinib versus platinum‐based double agent chemotherapy as the first‐line treatment in patients with advanced anaplastic lymphoma kinase (ALK)‐positive lung adenocarcinoma.MethodWe retrospectively analyzed data from 19 patients with advanced ALK‐positive lung adenocarcinoma who had received no previous systemic treatment for advanced disease. Seven patients received oral crizotinib at a dose of 250 mg twice daily; 12 patients were administered standard chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The details of our search results could be seen in the flow diagram (Figure 1 ). Among these 13 studies (including 11 non randomized control trials [NRCTs] and 2 randomized control trials [RCTs]), 3 studies described first-line therapies [ 7 , 16 , 17 ], 3 studies described second-line therapies [ 6 , 11 , 16 ] and 7 studies described mixed therapies [ 5 , 10 , 12 – 15 , 19 ]. Moreover, 8 studies reported median PFS and 95% CI [ 5 7 , 10 , 13 , 15 , 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The details of our search results could be seen in the flow diagram (Figure 1 ). Among these 13 studies (including 11 non randomized control trials [NRCTs] and 2 randomized control trials [RCTs]), 3 studies described first-line therapies [ 7 , 16 , 17 ], 3 studies described second-line therapies [ 6 , 11 , 16 ] and 7 studies described mixed therapies [ 5 , 10 , 12 – 15 , 19 ]. Moreover, 8 studies reported median PFS and 95% CI [ 5 7 , 10 , 13 , 15 , 16 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of studies have shown that the ALK-targeted inhibitor crizotinib produces a prominent positive effect in patients harboring an ALK rearrangement [14,15]. In January 2013, crizotinib was approved by the Sino Food and Drug Administration (SFDA) in mainland China for patients with ALK -positive NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…[4]Ceritinib1021000000000Cui, S. [17]Crizotinib72103000500000Felip, E. [5]Ceritinib124NA17NANANANANANANANANAMok, T. [6]Ceritinib1406422NANANA698NANANACui, S. [18]Crizotinib5682000500000Kim, D. W. [7]Ceritinib24612573010121115150816Ou, Sai-Hong [8]Alectinib138382NA411100NANAShaw, A. T. [9]Alectinib87355130000000Zhang, Q. [19]Crizotinib711000000000 NA not available …”
Section: Resultsmentioning
confidence: 99%